DETERMINING THE INJURY PATTERN AND ASSOCIATED RISK FACTOR OF INJURY AMONG FRISBEE ATHLETES IN MALAYSIA - Fairus Fariza Zainudin; Muhammad Danish Amin Borhanuddin; Nor Fadila Kasim (INTERNATIONAL JOURNAL OF EDUCATION, PSYCHOLOGY AND COUNSELLING (IJEPC), 2025)
Ultimate Frisbee is a non-contact sport gaining popularity in Malaysia. As a physically demanding competition, it can result in unavoidable injuries. However, data on injury profiles in Malaysia remain lacking, and the severity of injuries remains unknown. Therefore, this study aims to determine the injury pattern, anatomical location, severity, and associated risk factors for Ultimate Frisbee athletes in Malaysia. A cross-sectional survey was conducted using an online self-reported questionnaire from athletes registered under the Malaysian Ultimate Frisbee Association in 2022. Data were collected on types of injury (new or recurrent; soft tissue or hard tissue), location, nature, severity, and risk factors (self-induced, third-party, equipment, or environment). 137 athletes responded voluntarily (60% male, 40% female); mean participant age was 24.84 (±4.68) years, and mean Body Mass Index (BMI) was 21.44 (±1.99) kg/m². 95.2% participated actively in Frisbee competitions in the previous year at university (52.4%), national (13.8%), and international (4.1%) levels. Most injuries occurred during competition or training (n = 130), and more than 62% of injuries caused athletes to stop playing. The most common sites of injury for the lower limbs were the knee and ankle, followed by the wrist, shoulder, and elbow/upper arm for upper limbs. Only 3.5% reported spinal injuries, and 7 cases reported injuries to the head/face. 62% of reported cases were recurrent injuries, and 8% involved fractures and dislocations. Risk factors associated with injury included body composition, inadequate warm-up, lack of equipment safety, opponents, and playing surface. In conclusion, this study demonstrated that most injuries occur in the lower limbs, with minor injuries but a high rate of recurrence. The findings suggest that not only is on-site emergency treatment needed, but also prolonged, complete sports rehabilitation programs to reduce the incidence of recurrent injuries and lessen the likelihood of injury severity.